What Kurt Schneider really said and what the DSM has made of it in its different editions: a plea to redefine hallucinations in schizophrenia - Moritz, Steffen; Gawęda, Łukasz; Carpenter, William T; Aleksandrowicz, Adrianna; Borgmann, Lisa; Gallinat, Jürgen; Fuchs, Thomas (Schizophrenia bulletin, 2024)
Kurt Schneider has played a leading role in shaping our current view of schizophrenia, placing certain manifestations of delusions and hallucinations at the center of the disorder, especially ideas of persecution and voice-hearing. The first part of this review summarizes Schneider’s original ideas and then traces how the different editions of the DSM merged aspects of Kraepelin’s, Bleuler’s, and Schneider’s historical concepts. Special attention is given to the transition from the DSM-IV to the DSM-5, which eliminated much of Schneider’s original concept. In the second part of the article, we contrast the current definition of hallucination in the DSM-5 with that of Schneider. We present empirically derived arguments that favor a redefinition of hallucinations, much in accordance with Schneider’s original ideas. We plea for a two-dimensional model of hallucinations that represents the degree of insight and perceptuality, ranging from thoughts with full “mineness” via perception-laden thoughts and intrusions (including “as if” experiences”) to hallucinations. While we concur with the DSM-5 that cognitions that are indistinguishable from perceptions should be labeled as hallucinations, we suggest expanding the definition to internally generated sensory phenomena, including those with only partial resemblance to external perceptions, that the individual considers real and that may lie at the heart of a subsequent delusional superstructure.
Online veröffentlicht: 21. September 2023
Gesehen am 28.08.2024